Monodisperse Carbon Nanospheres with Hierarchical Porous Structure as Electrode Material for Supercapacitor - Yang, Xiutao (Nanoscale Res Lett, 2017)
Carbon nanospheres with distinguishable microstructure were prepared by carbonization and subsequent KOH activation of F108/resorcinol-formaldehyde composites. The dosage of triblock copolymer Pluronic F108 is crucial to the microstructure differences. With the adding of F108, the polydisperse carbon nanospheres (PCNS) with microporous structure, monodisperse carbon nanospheres (MCNS) with hierarchical porous structure, and agglomerated carbon nanospheres (ACNS) were obtained. Their microstructure and capacitance properties were carefully compared. As a result of the synergetic effect of mono-dispersion spheres and hierarchical porous structures, the MCNS sample shows improved electrochemical performance, i.e., the highest specific capacitance of 224 F g(−1) (0.2 A g(−1)), the best rate capability (73% retention at 20 A g(−1)), and the most excellent capacitance retention of 93% over 10,000 cycles, making it to be the promising electrode material for high-performance supercapacitors.